Rancang Bangun Lampu Inframerah Standing Arm Menggunakan Sensor Jarak Dan Timer - Putri, Suci Imani; Ferdana, Nanda; Suhartina, Rahmalisa; Firdaus, Ade (Innovative: Journal Of Social Science Research, 2024)
Infrared therapy is a joint and muscle therapy that relies on red light. Infrared lights can emit waves that penetrate body tissue, thus providing a number of health benefits. The author's goal is to design a standing infrared lamp using a proximity sensor and timer. The system is designed to improve energy efficiency and user comfort by automatically controlling the lights based on the presence and activity around them. The main components of this system include the HC-SR04 proximity sensor which functions to detect the distance of the object, and a microcontroller which functions to regulate the duration of infrared irradiation. The results of the research show that the distance was tested 10 times and for each distance 5 trials were carried out, showing that the tool showed a distance measurement error of 0.162%. And the time settings provided by the tool were carried out by changing the time settings provided by the tool, namely for 5, 10, 15, 20, 25 and 30 minutes and each experiment was carried out 5 times, showing a time measurement error of 24.8 seconds.